Measurement of X-ray spectra using a Lu2(SiO4)O-multipixel-photon detector with changes in the pixel number. (September 2015) - Yamaguchi, Satoshi; Sato, Eiichi; Oda, Yasuyuki; Nakamura, Ryuji; Oikawa, Hirobumi; Yabuushi, Tomonori; Ariga, Hisanori; Ehara, Shigeru
Abstract: To measure X-ray spectra with high count rates, we developed a detector consisting of a Lu2 (SiO4 )O [LSO] crystal with a decay time of 40 ns and a multipixel photon counter (MPPC). The photocurrents flowing through the MPPC are converted into voltages and amplified by a high-speed current–voltage amplifier, and event pulses from the amplifier are sent to a multichannel analyzer to measure spectra. We used three MPPCs of 100, 400 and 1600 pixels/mm 2, and the MPPCs were driven under pre-Geiger mode at a temperature of 20 °C. At a tube voltage of 100 kV and a tube current of 5.0 μA, the maximum count rate was 12.8 kilo-counts per second. The event-pulse widths were 200 ns, and the energy resolution was 53% at 59.5 keV using a 100-pixel MPPC. Highlights: Zero-dark-counting X-ray detection was performed under pre-Geiger mode. 200-ns-width event pulses were produced by a high-speed amplifier. X-ray spectra were measured using three LSO-MPPC detectors. Energy resolution improved with decreasing MPPC pixel number.